Senior Managers’ Perceptions of Audit Committee Composition and Effectiveness: Some Evidences from Malaysia - Moho Saad, Siti Shaharatulfazzah; Evans, Jonathan Gary; Muhamad Sori, Zulkarnain (INTI Publishing House Sdn. Bhd., 2006)
The aim of this study is to investigate the perceptions of corporate management of audit committee composition and effectiveness. Issues examined include status of audit committee members, members’ knowledge of financial matters, status of the chairman of audit committee, and characteristics of an effective audit committee. It has been found that the effectiveness of the audit committee would be enhanced if the committee comprised a majority of non-executive directors. The respondents also believed that the effectiveness of the audit committee would be enhanced if the majority of the audit committee members were knowledgeable in financial matters and the non- executive director assumed the chairmanship of the committee, It is also found that a characteristic of a good audit committee is its members have a good knowledge and understanding of the company’s business activities.